Caffeine in liver diseases: Pharmacology and toxicology - Shan, Liang; Wang, Fengling; Zhai, Dandan; Meng, Xiangyun; Liu, Jianjun; Lv, Xiongwen (Frontiers in Pharmacology, 2022)
We have previously shown that adenosine A1AR antagonists, adenosine A2aAR antagonists, and caffeine have significant inhibitory effects on the activation and proliferation of hepatic stellate cells in alcoholic liver fibrosis. Many recent studies have found that moderate coffee consumption is beneficial for various liver diseases. The main active ingredient of coffee is caffeine, which is a natural non-selective adenosine receptor antagonist. Moreover, numerous preclinical epidemiological studies and clinical trials have examined the association between frequent coffee consumption and the risk of developing different liver diseases. In this review, we summarize and analyze the prophylactic and therapeutic effects of caffeine on various liver diseases, with an emphasis on cellular assays, animal experiments, and clinical trials. To review the prevention and treatment effects of caffeine on different liver diseases, we searched all literature before 19 July 2022, using “caffeine” and “liver disease” as keywords from the PubMed and ScienceDirect databases. We found that moderate coffee consumption has beneficial effects on various liver diseases, possibly by inhibiting adenosine binding to its receptors. Caffeine is a potential drug for the prevention and treatment of various liver diseases.